Seawater ecotoxicity of monoethanolamine, diethanolamine and triethanolamine - LIBRALATO, Giovanni; VOLPI GHIRARDINI, Annamaria; AVEZZU', Francesco (Journal of Hazardous Materials, 2010)
Monoethanolamine (MEA), diethanolamine (DEA) and triethanolamine (TEA) are compounds with potential acute, sub-chronic and chronic toxicity effects towards aquatic species.Aliterature review highlighted the existence of a gap in the knowledge on their toxicity with saltwater testing species. A battery of toxicity tests including the alga Phaeodactylum tricornutum Bohlin, the bivalve molluscs Crassostrea gigas (Thunberg) and Mytilus galloprovincialis (Lmk), and the crustacean Artemia franciscana, was considered to update and improve the existing ecotoxicological information. Data were provided as the Effective Concentration that induces a 50% effect in the observed population (EC50), Lowest Observed Effect Concentration (LOEC) and No Observed Effect Concentration (NOEC). EC50, LOEC and NOEC values were compared with a reviewed database containing the existing ecotoxicological data from saltwater organisms.